Spontaneous Emission Enhancement of CdSe Quantum Dots Embedded in a Two-dimensional Photonic Crystal L3 Nanocavity - Sediq, Khalid N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Two-dimensional photonic crystal nanocavities were designed to tailor cavity quantum electrodynamics. Enhancing the spontaneous emission of low-quality factor nanocavity with embedded CdSe quantum dots (QDs) emitters is the aim of this study. Low concentration layer of CdSe QDs was sandwiched between two layers of Si2 N3 membrane using plasma-enhanced chemical vapor deposition. The modification rate in spontaneous emission of L3 nanocavity up to 2.3-fold has been observed at 629.5 nm in compare to bare cavities. High field confinement in the sub-wavelength regime became an interest field for quantum electrodynamics applications and good platform to study light matter interactions.